2013
DOI: 10.1111/odi.12193
|View full text |Cite
|
Sign up to set email alerts
|

Urban legend series: mucous membrane pemphigoid

Abstract: Mucous membrane pemphigoid (MMP) is a heterogeneous group of autoimmune subepithelial blistering diseases affecting primarily mucous membranes showing marked degree of clinical and immunological variability. We investigated four controversial topics: (i) Does oral pemphigoid (OP) really exist as a separate entity? (ii) Is mucous membrane pemphigoid curable? (iii) What is the best therapeutic option for MMP? (iv) Does exclusive oral IgA dermatitis exist as a distinct entity from MMP? Results from extensive lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 143 publications
(142 reference statements)
1
20
0
4
Order By: Relevance
“…In addition, other studies report reactivity against the C‐terminal domain of BP180 . Although no clear association between target antigens and a specific clinical phenotypes has been reported, some studies have suggested an association between ocular pemphigoid and the β4 integrin, while a possible association between oral disease and α6 integrin has been proposed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies report reactivity against the C‐terminal domain of BP180 . Although no clear association between target antigens and a specific clinical phenotypes has been reported, some studies have suggested an association between ocular pemphigoid and the β4 integrin, while a possible association between oral disease and α6 integrin has been proposed …”
Section: Discussionmentioning
confidence: 99%
“…24,27,28 Although no clear association between target antigens and a specific clinical phenotypes has been reported, some studies have suggested an association between ocular pemphigoid and the b4 integrin, while a possible association between oral disease and a6 integrin has been proposed. [29][30][31][32][33][34] It is unclear why bullous pemphigoid (BP), a predominantly cutaneous disease, and MMP share the same target epitope, BP180-NC16a, yet have a different clinical phenotype and disease course. Differences may relate to additional epitopes on BP180 being targeted, additional antigens being targeted (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence to guide therapy in MMP. 27,28 For mild to moderate oral disease, topical treatments may be used as mouthwashes (betamethasone 0.5 mg or fluticasone propionate 400 lg in ª 2019 British Association of Dermatologists 10 mL of water as a 3-min rinse) or pastes (clobetasol propionate in Orabase as a 50% mix) applied either directly or in a custom-made dental tray. Maintenance of good oral hygiene is paramount, as plaque may compound gingival inflammation.…”
Section: Treatmentmentioning
confidence: 99%
“…Neoplastic disorders (detailed at baseline) were: breast cancer (n=3), melanoma (1), lung cancer (1), and prostate cancer (2). Medications taken were principally anti-hypertensive (22.1%) and anxiolytics (7.9%).…”
Section: Resultsmentioning
confidence: 99%
“…There is an evident degree of variability in the clinical and immunological features of MMP, suggesting the existence of multiple phenotypic variants (2). From a diagnostic and therapeutic view, it might be of significant advantage to discriminate a clinical subset of MMP, termed oral pemphigoid, in which the disease is mainly limited to the oral cavity and patients have a better prognosis compared to other variants (3).…”
Section: Introductionmentioning
confidence: 99%